Hungarian Monitoring, 5 February 1990 . [Magyar rádiófigyelő], 1990. február 5 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - CPSU Central Committee plenum begins - ANC conference - Gorbachev: "The CPUS should give up its leading role!" - Now settlement plan for Afghanistan Domestic Affairs: - Hungarian-Romanian cultural cooperation agreement - László Tőkés's schedule in Gyula - Soviet troop withdrawals - Situation of Hungarian minorities in Romania and Czechoslovakia - Election programs Economy: - Péter Medgyessy's economic talks in Paris - Mineral oil from Iraq Külpolitika: - Megkezdődött az SZKP KB-plénuma - Az Afrikai Nemzeti Kongresszus tanácskozása - Gorbacsov: "Az SZKP mondjon le vezető szerepéről!" - Az Afganisztánnal kapcsolatos új rendezési terv Belpolitika: - Magyar-román kulturális együttműködési megállapodás - Tőkés László gyulai programja - Szovjet csapatkivonás - Magyar kisebbségek helyzete Romániában és Csehszlovákiában - Választási műsorok Gazdaság: - Medgyessy Péter párizsi gazdasági megbeszélései - Kőolaj Irakból